Roofing the right way : a step-by-step guide for the homeowner - Bolt, Steven, 1949- (Tab Books, 1986)
Do it yourself and do it right with the definitive step-by-step roofing manual. If you want to save up to 60 percent, or even more, on roofing repairs or replacement, this book can help you. It's like having a professional at your side to prevent mistakes that could be costly. Even roofing apprentices and construction professionals can learn from the information and advice inside this best-selling guide. Completely updated with new material and illustrations, this editon gives Full details on the newest tools and materials Inside information on all the latest roofing techniques used by professionals Step-by-step instructions on roof repair and installation Clear work-in-progress illustrations Precise descriptions of application patterns Complete details on concrete tile roofing and other hot trends Tips on choosing a contractor Detailed field studies and best practice information A useful appendix contains answers to frequently asked questions. In addition, you'll find comprehensive lists for sources of products and tools, and information on roofing associations and institutes